1900
DOI: 10.5962/bhl.title.965
|View full text |Cite
|
Sign up to set email alerts
|

Adephagous and clavicorn Coleoptera from the Tertiary deposits at Florissant, Colorado, with descriptions of a few other forms and a systematic list of the nonrhynchophorous Tertiary Coleoptera of North America

Abstract: GOVERNMENT PRINTING OFFIOE (forty-four genera (six extinct), vi/, eighty-five species of thirty-four genera (five extinct) in the ()ld World, and thirtv-three species of twentv-six genera (one extinct) in the New World. No species have been found on both continents. ()f the fortv-four genera from the older Tertiaries, thirl vfour are found in the Old World, nineteen in the New, and nine in both. Fourteen genera are represented both in the older and latest Tertiaries. OYOIIKTS Fabricius. The only fossil specie^… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 0 publications
0
37
0
2
Order By: Relevance
“…Five more Cenozoic species of Stenus are rock fossils described from Eocene (USA) and Oligocene (France and Germany)38. Even though their preservation is rather poor, they also clearly resemble recent Stenus 3940414243. The only non- Stenus fossil described from Cenozoic is the extinct genus Eocenostenus Cai, Clarke, Huang & Nel, 2014 from the late Eocene of Alès-Monteils (France).…”
Section: Fossil Record Of Steninae and Presumably Related Subfamiliesmentioning
confidence: 99%
“…Five more Cenozoic species of Stenus are rock fossils described from Eocene (USA) and Oligocene (France and Germany)38. Even though their preservation is rather poor, they also clearly resemble recent Stenus 3940414243. The only non- Stenus fossil described from Cenozoic is the extinct genus Eocenostenus Cai, Clarke, Huang & Nel, 2014 from the late Eocene of Alès-Monteils (France).…”
Section: Fossil Record Of Steninae and Presumably Related Subfamiliesmentioning
confidence: 99%
“…Originally, the remains from the Pleistocene peatbog or asphalt deposits were assigned to extinct species by historical authors (e.g. Łomnicki 1894, Grinell 1908, Orchymont 1927, Pierce 1946, 1948, 1949, 1954, Scudder 1900), supporting the idea of a high evolutionary rate induced by the climate changes during the Pleistocene. Later, more detailed studies of subfossil specimens sometimes based even on the study of their well-preserved genitalia revealed that the majority of Pleistocene subfossil beetles belong to recent species (Elias 2010; for examples of taxonomic revisions see e.g., Darlington 1938, Angus 1973, 1997, Miller and Peck 1979, Doyen and Miller 1980, Miller et al 1981) and resulted in the Pleistocene evolutionary stasis paradigm (Coope 1970, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…The fossil was described as belonging to the extant genus Mataeopsephus , and possibly belonging to the extant M. japonicus , which currently occurs in Japan (Fujiyama 1983). One adult fossil beetle was described as Psephenus lutulentus Scudder, 1900 from the late Eocene of Florissant, USA (Scudder 1900), but there are doubts concerning its correct identification (Fujiyama 1983). Besides these two fossil records of psephenids that fall into the biogeographical range of the extant taxa, there are two fossil records of eubrianacine species from Europe where no extant species of this group occur nowadays (Bertrand and Laurentiaux 1963; Lutz 1985, 1990).…”
mentioning
confidence: 99%